A Randomized, Open-Label Trial to Evaluate Switching to Elvitegravir/Cobicistat/Emtricitabine/Tenofovir Alafenamide Plus Darunavir in Treatment-Experienced HIV-1-Infected Adults. (1st February 2017) - Huhn, Gregory D.; Tebas, Pablo; Gallant, Joel; Wilkin, Timothy; Cheng, Andrew; Yan, Mingjin; Zhong, Lijie; Callebaut, Christian; Custodio, Joseph M.; Fordyce, Marshall W.; Das, Moupali; McCallister, Scott
Abstract : Background: HIV-infected, treatment-experienced adults with a history of prior resistance and regimen failure can be virologically suppressed but may require multitablet regimens associated with lower adherence and potential resistance development. Methods: We enrolled HIV-infected, virologically suppressed adults with 2-class to 3-class drug resistance and at least 2 prior regimen failures into this phase 3, open-label, randomized study. The primary endpoint was the percentage of participants with HIV-1 RNA <50 copies per milliliter at week 24 [Food and Drug Administration (FDA) snapshot algorithm]. Results: For 135 participants [elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide (E/C/F/TAF) plus darunavir (DRV), n = 89; baseline regimen, n = 46], most of whom were taking a median of 5 tablets/d, simplification to E/C/F/TAF plus DRV was noninferior to continuation of baseline regimens at week 24 (plasma HIV-1 RNA <50 copies per milliliter: 96.6% vs. 91.3%, difference 5.3%, 95.001% CI: −3.4% to 17.4%). E/C/F/TAF plus DRV met prespecified criteria for noninferiority and superiority at week 48 for the same outcome. E/C/F/TAF plus DRV was well tolerated and had an improved renal safety profile compared with baseline regimens, with statistically significant differences between groups in quantitative total proteinuria and markers of proximal tubular proteinuria. Compared with baseline regimens, participants who switched to E/C/F/TAF plus DRV reported higher mean treatment satisfaction scale total scores and fewer days with missed doses. Conclusions: This study demonstrated that regimen simplification from a 5-tablet regimen to the 2-tablet, once-daily combination of E/C/F/TAF plus DRV has durable maintenance of virologic suppression and improvements in specific markers of renal safety. Such a strategy may lead to greater adherence and improved quality of life. Abstract : Supplemental Digital Content is Available in the Text.